2006
DOI: 10.5664/jcsm.26656
|View full text |Cite
|
Sign up to set email alerts
|

An Initial Report of Sleep Disturbance in Inactive Inflammatory Bowel Disease

Abstract: Background:There is an increased prevalence of gastrointestinal symptoms, peptic ulcer disease, and colon cancer in night-shiftworkers, whose sleep is commonly disrupted. Sleep complaints are an extrapyramidal symptom of irritable bowel syndrome (IBS). Sleep disruption may contribute to increased medical morbidity by weakening the ability of the immune system to protect against endotoxins-this pathway could be of potential importance to the pathogenesis and/or clinical course of inflammatory bowel disease (IBD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
78
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 117 publications
(81 citation statements)
references
References 53 publications
2
78
1
Order By: Relevance
“…The most common objective sleep measure among these studies (15/16) was PSG, and only two studies employed actigraphy. 22,23 Five studies used only subjective sleep measures, 8,10,[12][13][14] three studies used only PSG, [24][25][26] and the remaining 13 studies 11,15,22,23,[27][28][29][30][31][32][33][34][35] used at least one subjective and one objective sleep measure. Frequent awakening was also an important concern for patients with IBS in a study by Ranjbaran et al 14 Childhood abuse and neglect seems to influence the sleep quality in women with IBS; whereas little is known about men with IBS.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The most common objective sleep measure among these studies (15/16) was PSG, and only two studies employed actigraphy. 22,23 Five studies used only subjective sleep measures, 8,10,[12][13][14] three studies used only PSG, [24][25][26] and the remaining 13 studies 11,15,22,23,[27][28][29][30][31][32][33][34][35] used at least one subjective and one objective sleep measure. Frequent awakening was also an important concern for patients with IBS in a study by Ranjbaran et al 14 Childhood abuse and neglect seems to influence the sleep quality in women with IBS; whereas little is known about men with IBS.…”
Section: Resultsmentioning
confidence: 99%
“…31 However, in this review inconsistent findings on the relationship of psychological factors to subjective sleep were found. For example, researchers 8,14,15,27,[30][31][32][33][34][35] reported that psychological factors (e.g., anxiety, depression, or stress) influenced the degree of subjective report differences between IBS and the con- In addition to alterations in REM sleep, there is some evidence that persons with IBS spend increased time in light sleep (Stages 1 and 2). 33 Given that arousal/awakenings occur more easily in light sleep, this alteration might explain the increased frequency of reported arousal/ awakenings in persons with IBS.…”
Section: Subjective Measures Of Sleep In Ibsmentioning
confidence: 99%
See 2 more Smart Citations
“…[1][2][3][4][5] Multiple visceral disorders, including in the gastrointestinal system, also follow sleep disturbances in humans. [6][7][8][9] However, probably because of the large changes in cerebral electrical activity which accompany transition from wakefulness to sleep most basic studies of sleep have been mainly focused on various aspects of cerebral functions, as reviewed in several recent publications. [10][11][12] It is generally recognized at present that, during periods of slow-wave sleep, cortical neurons change their firing mode to a synchronized burst-pause pattern, shown by slow waves in EEG recordings.…”
Section: Introductionmentioning
confidence: 99%